Total tubular triplication of colon - Michaela Gaffley; Alan A. Reyes Cruz; Lucas P. Neff; José Uriel Ferrufino (Journal of Pediatric Surgery Case Reports, 2020)
Total tubular triplication of the colon is rare, with 9 cases reported so far in the world literature. We present a male patient born at 38 weeks and found to have total triplication of his colon. We call for clinician reporting of this rare anomaly to grow the literature base and aid diagnosis and treatment. Keywords: Anorectal malformation, Congenital abnormalities, Tubular triplication of the colon